Respon Pertumbuhan Bibit Kakao (Theobroma Cacao L.) Terhadap Perlakuan Kombinasi Pupuk NPK dengan Kompos POME pada Tanah Ultisol di Polybag - Ridawati Marpaung; Rudi Hartawan; Jippo Daniel Manurung (Universitas Batanghari, 2026)
This study aims to obtain the best combination dose of NPK 16-16-16 fertilizer and solid palm oil compost to support the growth of cocoa seedlings (Theobroma cacao L.) in polybag planting media. The study used a one-factor Completely Randomized Design (CRD) with a combination treatment design of NPK 16-16-16 fertilizer with solid palm oil compost (s) with 6 levels. 3 kg of ultisol soil/polybag as follows, s0 (3 kg of ultisol soil/polybag); s1 (100% NPK 16-16-16 (8g/polybag) ; s2 (100% solid palm oil compost (200g/polybag) ; s3 (75% NPK 16-16-16 (6g/polybag) + 25% solid palm oil compost (50g/polybag)) ; s4 (50% NPK 16-16-16 (4g/polybag) + 50% solid palm oil compost (100g/polybag) ; s5 (25% NPK 16-16-16 (2g/polybag) + 75% solid palm oil compost (150g/polybag). Based on the analysis of variance, it shows that the combination of NPK 16-16-16 fertilizer and solid palm oil compost has a significant effect on the parameters of plant height, leaf area, leaf color, dry weight of the crown, and the ratio of the root crown but has no significant effect on the stem diameter, weight dry roots, and cocoa seedling quality index. Treatment s2 (100% solid compost 200g) gave the highest average value for all observation parameters